The role of intellectual humility in promoting epistemic fluency for interdisciplinary engineering education - Sivakumar, Kishore; Boon, Mieke (Frontiers in Education, 2024)
Interdisciplinary engineering education aims to equip engineers with the ability to tackle complex real-world problems that occur beyond traditional disciplinary boundaries, therefore demanding a set of interdisciplinary competencies. In our research on interdisciplinary competence, a study consisting of interviews with teachers and researchers focusing on Higher Order Thinking Skills (HOTS) necessary for interdisciplinary research purposes, revealed that the interviewees emphasize specific attitudinal aspects as important for being competent in interdisciplinary research contexts. Notably, the attitudinal aspects as described by the interviewees can be understood through the notion of intellectual humility (IH). This observation motivated an exploratory literature review, which led to the conceptualization of IH as an attitude consisting of the ability to recognize one’s intellectual limitations and openness to alternative perspectives and clarified its potential role in the development of epistemic fluency, as an interdisciplinary competence that integrates knowledge, skills and attitude. The refined conceptual understanding of IH along with the empirical findings on the importance of IH resulting from the interviews with experts in interdisciplinary engineering education, supports the view of IH as a crucial attitude for epistemic fluency in interdisciplinary education contexts, together with the importance of awareness and knowledge of disciplinary perspectives. Epistemic fluency, in turn, is conceptualized as a key interdisciplinary competency that integrates knowledge (disciplinary perspectives), attitudes (IH), and skills (HOTS). Finally, suggestions are made for possible ways to promote IH as part of this competence.